Repetitive somatic embryogenesis and plant regeneration in Garcinia indica Choiss - Thengane, Shubhada Ratnakar; Deodhar, Swapna R.; Bhosle, S. V.; Rawal, S. K. (In Vitro Cellular & Developmental Biology-Plant, 2006)
Immature seeds of Garcinia indica Choiss. were excised from immature fruits and cultured on Lloyd and McCown (1980), woody plant medium (WPM) with different combinations of auxins and cytokinins. Somatic embryos were obtained on the media supplemented with 6-benzylaminopurine (BA; 2.2-22.1 mu M) alone or in combination with alpha-naphthalene acetic acid (NAA; 2.6 mu M) with 80% frequency within a period of 2-3 wk. Subculture of embryos on medium containing BA (16.0 mu M) supplemented with indole-3-acetic acid (IAA; 2.8-5.7 mu M) and/or kinetin (4.6 mu M) gave rise to clusters of secondary somatic embryos along with maturation of primary embryos. In subsequent subculture on hormone-free half-strength WPM, the embryo clusters germinated with an increase in the number of secondary somatic embryos. About 70% of somatic embryos germinated into complete plantlets, which were successfully established under greenhouse conditions.
Keywords: Garcinia indica; guttifereae; secondary somatic embryos; seeds; somatic embryos

Recurrent somatic embryogenesis and plant regeneration in Angelica glauca Edgew., a critically endangered medicinal plant of the Western Himalaya - Pandey, Meena; Dhar, Uppeandra; Samant, Sher Singh; Shirgurkar, Mrudul Vijay; Thengane, Shubhada Ratnakar (Journal of Horticultural Science & Biotechnology, 2011)
Secondary somatic embryogenesis and plant regeneration from seedling explants of Angelica glauca, an endangered medicinal plant of the Himalaya, is reported for the first time. Callus was obtained from all the explants tested in the present study (i.e., epicotyls, hypocotyls, and cotyledonary nodes). The highest frequency of callus formation (95.8%) was observed using epicotyl explants on 4.0 mu M 2,4-dichlorophenoxyacetic acid (2,4-D), whereas 70.8% of hypocotyl explants, and 58.3% of cotyledonary nodes produced callus. One-hundred percent embryogenic callus was induced from epicotyl explants in 2.0 mu M 6-benzyladenine (BA) and 2.0 mu M alpha-naphthaleneacetic acid (NAA), together with the maximum number of somatic embryos (34.2 embryos per explant). Cotyledonary nodes did not produce somatic embryos. Histological studies confirmed the induction of somatic embryogenesis. Somatic embryos germinated into plantlets upon transfer to half-strength Murashige and Skoog (MS) medium without added plant growth regulators. We observed 85% survival of these plantlets under field conditions. The development of secondary embryos was also observed when primary embryos were sub-cultured on full-strength MS medium containing 2.0 mu M NAA plus 2.0 mu M BA. This system of recurrent somatic embryogenesis provides a route for gene transfer and also for the large-scale production of this critically endangered medicinal plant.